Spatial Decision Support System based on Multicriteria Decision Analysis and Spatial Information for Flood Management Planning: Location Analysis for Construction of New Hospital Building in Kelantan, Malaysia - Abdullah, Mohammad Fikry; Zainol, Zurina; Md Shah, Amri (2023)
The frequent occurrence of floods in Kelantan, Malaysia, necessitates effective flood management planning, especially in the construction of critical infrastructure like hospitals. This study presents a Spatial Decision Support System (SDSS) prototype that integrates Multicriteria Decision Analysis (MCDA) and spatial information to identify feasible locations for a new hospital building in floodprone areas of Kelantan. The proposed SDSS aims to enhance flood resilience and improve emergency response capabilities in the region. Using the SDSS, four MCDA techniques were employed to rank three proposed locations based on four Representative Concentration Pathway (RCP), namely RCP 2.6, 4.5, 6.0, and 8.5, for a period of 2010– 2039. A frequency analysis was then conducted for each location to determine its feasibility. Subsequently, validation of the recommended location using the Content Validity Index (CVI) was carried out by eleven experts to ensure its suitability. The findings demonstrate that the proposed SDSS enhances flood management planning by identifying sites with reduced flood risk based on identified flood decision criteria. Furthermore, the system aids in optimising resource allocation and strengthening the overall flood resilience of the healthcare infrastructure in Kelantan. The study's outcomes offer valuable insights for authorities, urban planners, and policymakers involved in flood management and infrastructure development in disaster-prone regions.